2021
DOI: 10.1111/1462-2920.15717
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio splendidus persister cells induced by host coelomic fluids show a similar phenotype to antibiotic‐induced counterparts

Abstract: Persister cells are dormant variants of regular cells that are multidrug tolerant and have heterogeneous phenotypes; these cells are a potential threat to hosts because they can escape the immune system or antibiotic treatments and reconstitute infectious. Skin ulcer syndrome (SUS) frequently occurs in the sea cucumber (Apostichopus japonicus), and Vibrio splendidus is one of the main bacterial pathogens of SUS. This study found that the active cells of V. splendidus became persister cells more readily in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…For amino acids, Lglutamic acid revived V. splendidus persister cells used for the shortest time, and for saccharides, D-galactose, maltose, mannose, and sorbitol woke up V. splendidus persister cells better than D-fructose, N-acetyl-D-glucosamine, and D-glucose. The different numbers of colonies emerged on the specific carbon source probably attributed to the high heterogeneity of V. splendidus persister cells in dormancy (14), which resulted in their heterogeneous waking up on different carbon sources, probably due to different metabolism of various carbon sources in V. splendidus. Consequently, the results of this study indicated that (1) V. splendidus persister cells woke up responding to nutrient incentives similar to P. aeruginosa and E. coli (17,18,36) (2) L-glutamic acid is the best amino acid to revive V. splendidus persister cells, which is specific to this bacterial species; this further strengthened the concept that different bacterial persister cells preferred to use different carbon sources to wake up (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For amino acids, Lglutamic acid revived V. splendidus persister cells used for the shortest time, and for saccharides, D-galactose, maltose, mannose, and sorbitol woke up V. splendidus persister cells better than D-fructose, N-acetyl-D-glucosamine, and D-glucose. The different numbers of colonies emerged on the specific carbon source probably attributed to the high heterogeneity of V. splendidus persister cells in dormancy (14), which resulted in their heterogeneous waking up on different carbon sources, probably due to different metabolism of various carbon sources in V. splendidus. Consequently, the results of this study indicated that (1) V. splendidus persister cells woke up responding to nutrient incentives similar to P. aeruginosa and E. coli (17,18,36) (2) L-glutamic acid is the best amino acid to revive V. splendidus persister cells, which is specific to this bacterial species; this further strengthened the concept that different bacterial persister cells preferred to use different carbon sources to wake up (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…V. splendidus persister cells were prepared by lysing active cells with high concentration of tetracycline 400 µg•ml −1 , according to our previous study (14). Briefly, 10 ml of overnight V. splendidus culture was mixed with 40 ml 2216E containing 2,000 µl of tetracycline stock solution, and the culture was incubated 4 h in a shaker with a shaking speed of 150 rpm.…”
Section: Selection Of Persister Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like the carbapenem resistant A. baumannii and P. aeruginosa, Vibrio spp. are also proven capable of assuming the spherical form and entering into dormancy under hostile conditions [ 93 ]. They can exist as persister cells as part of their antimicrobial resistance potential (see Section 5.4 ).…”
Section: Vibrio Sppmentioning
confidence: 99%